The use of classification methods for modeling the antioxidant activity of flavonoid compounds - Weber, Karen C.; Honorio, Kathia M.; Bruni, Aline T.; da Silva, Alberico B. F. (Springer, 2006)
A study using two classification methods (SDA and SIMCA) was carried out in this work with the aim of investigating the relationship between the structure of flavonoid compounds and their free-radical-scavenging ability. In this work, we report the use of chemometric methods (SDA and SIMCA) able to select the most relevant variables (steric, electronic, and topological) responsible for this ability. The results obtained with the SDA and SIMCA methods agree perfectly with our previous model, in which we used other chemometric methods (PCA, HCA and KNN) and are also corroborated with experimental results from the literature. This is a strong indication of how reliable the selection of variables is.
Keywords: flavonoid compounds; antioxidant activity; classification methods